Motion in Games: 5th International Conference, MIG 2012, Rennes, France, November 15-17, 2012, Proceedings - Kallmann, Marcelo; Bekris, Kostas (LNCS sublibrary. SL 6, Image processing, computer vision pattern recognition and graphics, 2012)
This book constitutes the refereed proceedings of the 5th International Workshop on Motion in Games, held in Rennes, France, in November 2012. The 23 revised full papers presented together with 9 posters and 5 extended abstracts were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on planning, interaction, physics, perception, behavior, virtual humans, locomotion, and motion capture.